On the Decadal Trend of Global Mean Sea Level and Its Implication on Ocean Heat Content Change - Fu, Lee-Lueng (Frontiers in Marine Science, 2016)
The variability of the trend of the global mean sea level (GMSL) on decadal scales is of great importance to understanding the long-term evolution of the GMSL. Trend determination is affected by the temporally correlated processes in the record, which have often not been properly accounted for in previous studies. The problem is treated here as one of optimal estimation weighted by the auto-covariance of the time series, which takes into account the various underlying time scales affecting trend estimation. On decadal scales, the estimated standard error of the trend determined from the GMSL record from radar altimetry is about 0.3 mm/yr, which is comparable to the widely quoted 0.4 mm/yr systematic error and cannot be neglected in the error budget. The time scale of the systematic errors is assumed to be much longer than decadal scale, over which the formal error of the trend estimate becomes dominant. The approach is also applied to determining steric sea level from altimeter-measured sea level and ocean mass estimated from the GRACE observations. The estimated trend error of steric sea level, 0.12 mm/yr, suggests that the change of the global ocean heat content over decadal scales can be estimated from space observations to an accuracy on the order of 0.1 W/m2. The difference between the steric sea level, estimated from Argo plus the estimated contribution from the deep ocean, and that from altimeter and GRACE, 0.18 ± 0.25 mm/yr, provides an estimate of the combined systematic errors of altimetry minus GRACE observations over the 10 year time span of overlapping Argo and GRACE data.